Integration of Circular Economy and Local Biopharmaca in the Production of Chemical Residue-Free Healthy Chicken Eggs in Panti Subdistrict, Jember - Lelono, Asmoro; Akhmad Rikhwan; Rizky Surya Wijaya; Adelia Nur Fahmi; Nurul Fajril Azizah; Farahdillah Rafiatul Nurhasanah; Arumiannisa Altamaputri (Jurnal Inovasi Sains dan Teknologi Untuk Masyarakat, 2026)
Native chicken farming in Suci Village, Jember, faces significant challenges, including high mortality rates due to extreme weather and a heavy reliance on chemical antibiotics, which triggers the risk of Antimicrobial Resistance. This community service program aims to implement the downstreaming of superior native chicken strains developed by the Avian Immunity research team through a "Zero Antibiotic" management system to achieve household food sovereignty. The methodology employed is participatory empowerment using the "Agent of Change Model" strategy, focusing on a pilot project unit in Gaplek Hamlet. Initiated on December 10, 2025, the program synergized with the Village Head, Hamlet Head, and local police (Bhabinkamtibmas), designating Adelia Nur Fahmi (a Biology student and KIP scholarship recipient) as the primary agent of change. The implementation phases included the construction of biosecurity-based semi-intensive housing, the introduction of superior strain chicks, training in probiotic-based fermented feed production, and the application of local feed additive herbal (turmeric and ginger) as natural immunomodulators. Results indicate a significant improvement in the partner's technical skills, evidenced by a livestock survival rate of 84%. Currently, the pilot unit has entered the production phase, providing healthy eggs as a high-quality animal protein source to prevent stunting at the household level. The high level of community enthusiasm and the village government's request to replicate the program for underprivileged families demonstrate the success of this model as a sustainable circular economy prototype for rural areas.